2023
DOI: 10.3390/ma16114142
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Electrolytic Oxidation Coatings of a 6061 Al Alloy in an Electrolyte with the Addition of K2ZrF6

Abstract: In this study, white thermal control coatings were produced on a 6061 Al alloy using plasma electrolytic oxidation (PEO). The coatings were mainly formed by incorporating K2ZrF6. The phase composition, microstructure, thickness, and roughness of the coatings were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), a surface roughness tester, and an eddy current thickness meter, respectively. The solar absorbance and infrared emissivity of the PEO coatings were measured using a UV–V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The F element did not exhibit a significant presence, potentially due to the short oxidation time. According to Tu’s study, F was found to enter the coating at the late stage of micro-arc oxidation [ 21 ]. The coating without Na 2 WO 4 and the coating without K 2 ZrF 6 share the same main elemental composition of alumina.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The F element did not exhibit a significant presence, potentially due to the short oxidation time. According to Tu’s study, F was found to enter the coating at the late stage of micro-arc oxidation [ 21 ]. The coating without Na 2 WO 4 and the coating without K 2 ZrF 6 share the same main elemental composition of alumina.…”
Section: Resultsmentioning
confidence: 99%
“…Materials 2024, 17, x FOR PEER REVIEW 9 of 12 found to enter the coating at the late stage of micro-arc oxidation [21]. The coating without Na2WO4 and the coating without K2ZrF6 share the same main elemental composition of alumina.…”
Section: Effect Of Different Additives On the Surface Structure And M...mentioning
confidence: 99%
See 1 more Smart Citation
“…The expansion of the functionality of thermally sprayed aluminum coatings after their modification using PEO processing has already been demonstrated previously [42][43][44][45][46][47][48]. For the same purpose, plasma or cold spray deposition of aluminum coatings is also used [49,50], and aluminum, steel and titanium are used as the substrates [51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 82%